DFT insights on the electronic and thermoelectric properties of CuGaTe2 under pressure. (1st September 2022) - Bu, Jinlong; Yang, Xuewen; Ge, Guixian; Yang, Gui; Yang, Jueming
Abstract: The band structures of CuGaTe2 are very sensitive to the variation of lattice parameters because of the strong interaction between the Cu- d and Te- p valence electrons near Fermi level. In our study, the band convergence appeared for CuGaTe2 under the pressure of 3.8 GPa. These converged bands would be propitious to improve the thermoelectric properties of n -type CuGaTe2 . Two factors lead to rapid band convergence. One is the energy level increased more rapidly at Γ point than the X point near conduction band minimum along with the increased pressure. The other factor is the rapidly decreased value of valence band maximum at X point relative to the value at Γ point. The thermoelectric performance could be improved because of the band convergence for n -type CuGaTe2 . Highlights: The band structure of CuGaTe2 is very sensitive to its lattice parameters. The rapid band convergence appeared at points of X and Γ after pressure imposed. These converged bands would be beneficial for improving thermoelectric property. Two factors lead to the band convergence at high symmetry points of Γ and X.